Far-Ultraviolet and X-ray observations of the reverse shock in the Small Magellanic Cloud supernova remnant 1E 0102.2-7219 - Sasaki, Manami; Gaetz, Terrance J.; Blair, William; Edgar, Richard; Morse, Jon; Plucinsky, Paul P.; Smith, Randall (Astrophysical Journal, 2006)
We present Far Ultraviolet Spectroscopic Explorer (FUSE) and X-Ray Multi-Mirror Mission (XMM-Newton) data for the reverse shock of the O-rich supernova remnant (SNR) 1E 0102.2-7219 in the Small Magellanic Cloud (SMC). The FUSE observations cover three regions with significantly different optical [O (III)] intensities, all associated with the relatively bright part of the X-ray ring. Emission lines of O (VI) lambda lambda 1032, 1038 are clearly detected in the FUSE spectra. The XMM-Newton EPIC MOS 1/2 spectra are dominated by strong emission lines of O, Ne, and Mg. By combining the O (VI) doublet emission with the O (VII) triplet and O (VIII) Ly alpha fluxes from the X-ray spectra and assuming a nonequilibrium ionization (NEI) model with a single ionization timescale for the spectra, we find an increase of the ionization timescale tau from north (tau approximate to 0.6 x 10(11) s cm(-3)) to southeast (tau approximate to 2 x 10(11) s cm(-3)). This is indicative of increasing density in the X-ray-bright ring, in good agreement with the optical [O (III)] emission, which is strongest in the southeast. However, if we assume a plane-parallel shock model with a distribution of ionization timescales, the O (VI) emission appears to be inconsistent with O (VII) and O (VIII) in X-rays. The analysis of the total X-ray spectra shows that there is no consistent set of values for the temperature and ionization timescale that can explain the observed line ratios for O, Ne, and Mg. This would be consistent with a structured distribution of the ejecta, as the O, Ne, and Mg would have interacted with the reverse shock at different times.
Keywords: shock waves; supernova remnants; ultraviolet : ISM; X-rays : individual (1E 0102.2-7219)